Analisis Perbandingan Kinerja Bank Umum Konvensional Dengan Bank Umum Syariah Di Indonesia - Kharima, Alvia Noor (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to determine the comparison of the performance of the Conventional Public Banks and the Syariah Public Banks in Indonesia. The data in this resesarch is derived from the annual reports of the financial of banks in 2014 by calculating the ratios of financial of banks. The result of this research shows that the performance of the Conventional Public Banks are better than the Syariah Public Banks, on the ratio of the CAR, NPM, ROA, ROE, Current Ratio, Quick Ratio, LDR, and NPL.Keywors: Bank Performance, Conventional Public Banks, Syariah Public Banks.